La cooperazione sociale nell'area metropolitana fiorentina : Una lettura dei bilanci d'esercizio delle cooperative sociali di Firenze, Pistoia e Prato nel quadriennio 2004-2007 - Luca Bagnoli; Massimo Cini (Firenze University Press, 2009)
This study proposes a reading of the financial statements of co-operatives operating within the Florentine metropolitan area, with a view to underscoring business aspects of a quantitative and monetary nature. The entrepreneurial nature of the co-operatives is taken as read, focusing as with any other corporate entity on assets and economic results as indicators of success. The financial statements were collected from co-operatives with their registered offices in the provinces of Florence, Prato and Pistoia for the financial years 2004-2007, and the accounts were then aggregated, reclassified and analysed. The observations on the resulting data are then broken down by province and by type of co-operative (A or B).
Keywords: Economia aziendale; Terzo settore; Gestione d'impresa